2014
DOI: 10.1016/j.jvs.2013.12.044
|View full text |Cite
|
Sign up to set email alerts
|

Experience with the sandwich technique in endovascular thoracoabdominal aortic aneurysm repair

Abstract: The sandwich technique is an off-the-shelf endovascular alternative to treat patients with TAAAs in an emergent setting. The combination of chimney grafts with a periscope configuration enables a rapid endovascular aneurysm exclusion with acceptable midterm results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…7 However, CSGs have long manufacturing times and are therefore inappropriate for symptomatic and ruptured TAAAs. Hybrid 8 and exclusively endovascular 9 procedures have been offered in urgent/emergent settings, but these techniques are burdened by high morbidity rates (around 35%) [9][10][11] and overall perioperative mortality (13%). 8 Sweet et al 12 in 2009 demonstrated that a "standardized" endograft could be applied to 88% of aortic shapes.…”
mentioning
confidence: 99%
“…7 However, CSGs have long manufacturing times and are therefore inappropriate for symptomatic and ruptured TAAAs. Hybrid 8 and exclusively endovascular 9 procedures have been offered in urgent/emergent settings, but these techniques are burdened by high morbidity rates (around 35%) [9][10][11] and overall perioperative mortality (13%). 8 Sweet et al 12 in 2009 demonstrated that a "standardized" endograft could be applied to 88% of aortic shapes.…”
mentioning
confidence: 99%
“…Also, these devices are not available in many centers in developing countries. Alternative "off the shelf " endovascular techniques, like parallel graft techniques and physician-modified fenestrated stent-grafts, involve the use of standard grafts with good short-term and mid-term results [9][10][11][12][13][14][15]. Considering the anatomy of our case, we deemed that the diameter and shape of the true lumen were inadequate to accommodate two chimney grafts for the CT and the SMA.…”
Section: Discussionmentioning
confidence: 96%
“…72 Recent reports showed that the technical success and 30-day mortality rates were 88 and 6.3%, respectively, and endoleaks and risk of visceral stent occlusion were more frequent as the number of chimney grafts increased. 73 TEVAR with CA coverage indicated for Crawford type I TAAA cases is safe and effective when the CA-SMA collateral circulation is present. Technical success was acceptable, but the 30-day mortality was 9.7% in a recent review, and the most common cause of death was visceral ischemia, which accounted for 30% of such cases.…”
Section: Thoracoabdominal Aortic Aneurysmmentioning
confidence: 99%